Temporal trends in treatment and outcomes of patients with acute coronary syndrome and concomitant moderate to severe renal failure. (25th November 2020) - Bossard, M; Witassek, F; Radovanovic, D; Moccetti, F; Erne, P; Rickli, H; Kobza, R; Cuculi, F
Abstract: Introduction: Limited information about the management and outcomes of patients with acute coronary syndromes (ACS) and moderate to severe renal failure (RF) is available owing to underrepresentation of this population in most studies. Methods: We evaluated the use of guideline-recommended therapies and in-hospital outcomes of totally 49'191 ACS patients with normal-mild renal failure (RF) (defined as eGFR >45ml/min/m 2 ) versus moderate-severe RF (eGFR <45ml/min/m 2 ) enrolled in the prospective Acute Myocardial Infarction in Switzerland (AMIS) cohort between 2002 and 2019 according to 2-year periods. Results: Overall, 3'478 (7.1%) patients had moderate-severe RF. They were older (65.2+12.9 versus 77.2+10.6 years) and had significantly more comorbidities (including heart failure, cerebrovascular and peripheral vascular disease). Moderate-severe RF patients received less frequently guideline-recommended drugs, including P2Y12 inhibitors, ACEI/ARBs and statins (p<0.0001). Between the first and last 2-year periods, the number of patients with moderate-severe RF and number of performed percutaneous coronary interventions (PCI) increased in this cohort (p-for-trend=0.001). At the same time, in-hospital mortality significantly decreased among ACS patients with and without RF (17.5% to 10.5% and 6.0% to 3.9%, respectively, p-for-trend=0.001 for both, see Figure). Similar trends were observed for other complications, namely cardiogenic shock and reinfarction. However, major bleedings increased significantly over time in patients with and without RF (p-for-trend=0.038 and <0.001, respectively). Conclusions: Outcomes of ACS patients with moderate to severe RF improved over the last two decades. Even though the rate of PCI increased in ACS patients with moderate-severe RF, they were less likely to receive guideline-recommended therapies and still suffer a high in-hospitality mortality (>10%). With respect to the increasing burden of ACS patients with RF, our study implicates that more efforts should be undertaken to further improve outcomes of those patients. Funding Acknowledgement: Type of funding source: None